2005
DOI: 10.1093/ps/84.5.764
|View full text |Cite
|
Sign up to set email alerts
|

In ovo feeding improves energy status of late-term chicken embryos

Abstract: Maintenance of glucose homeostasis during late-term embryonic development is dependent upon the amount of glucose held in reserve primarily in the form of glycogen in the liver and upon the degree of glucose generated by gluconeogenesis from protein first mobilized from amnion albumen and then from muscle. Insufficient glycogen and albumen will force the embryo to mobilize more muscle protein toward gluconeogenesis, thus restricting growth of the late-term embryo and hatchling. We hypothesize that administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
315
2
23

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(359 citation statements)
references
References 36 publications
19
315
2
23
Order By: Relevance
“…Based on chemical and physical features and dose of the injected substance, different site of injection (i.e. the embryo, the amnion, the allantois, the air cell or the yolk sac) and embryo age (0, 12, 17 or 18 days of incubation) have been used (Casas-Perez and Edens, 1995;Pilarski et al, 2005;Uni et al, 2005;Cheled-Shoval et al, 2011;Ebrahimnezhad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Based on chemical and physical features and dose of the injected substance, different site of injection (i.e. the embryo, the amnion, the allantois, the air cell or the yolk sac) and embryo age (0, 12, 17 or 18 days of incubation) have been used (Casas-Perez and Edens, 1995;Pilarski et al, 2005;Uni et al, 2005;Cheled-Shoval et al, 2011;Ebrahimnezhad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This period is associated with a reduced in initial body weight with respect to development of gastrointestinal tract (GIT), some organs and muscles, and thus, meat yield at market age (Mozdziak et al, 2002;Halevy et al, 2003;Bhuiyan et al, 2011). Therefore, the last period of incubation has become one of the critical periods for growth, developmental programming of digestive and metabolic organs and skeleton muscles and led to the development of in ovo feeding systems for poultry (Uni et al, 2005). It has been reported that, to reduce the negative effect of large hatching window and to increase performance, the use of some in ovo amino acid supplements (Tako et al, 2004;Kadam et al, 2008;Bakyaraj et al, 2011;Al-Daraj et al, 2012) are necessary in the last period of incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Direct manipulations include the in-ovo injection of growth hormones or factors (e.g. insulinlike growth factor), amino acids, carbohydrates or neuromuscular active drugs into the embryos or its embryonic membranes (Kocamis et al, 1998;Heywood et al, 2005;Uni et al, 2005;McEntee et al, 2006;Pitsillides, 2006).…”
Section: Introductionmentioning
confidence: 99%